Greenhouse gas emissions from Argentinian soybean products - Hilbert, Jorge Antonio; Camardelli, Ariana; Ponieman, Karen Debora (Society of Chemical Industry, 2025)
Soybean products play an important role in Argentina’s bioeconomy. Greenhouse gas (GHG) emissions from soybean byproducts have been widely assessed to meet sustainability requirements for soybean oil biodiesel, especially by decision makers in the private and public sectors, in response to growing EU and USA market demands. Previous studies have focused primarily on GHG emissions from soybean cultivation and biodiesel production but not on the main byproducts like soy oil and meal. Over the past 15years, we have participated in these calculations, with methods certifed by independent verifcation bodies. Using real feld data, this study presents the total GHG emissions of Argentina’s main soybean products taking into account agriculture, biorefnery, and distribution stages and following EU Renewable Energy Directives I and II (EU RED I and II). The aim of the study was to assess the GHG emissions of Argentina’s soybean-producing chain through an integrated life cycle approach, applying mass and energy allocation methods. The results indicate that GHG emissions from soybean cultivation ranged from 186 to 266 kgCO2eq per ton of dry soybean, and from 9 to 13 gCO2eq per MJ of biodiesel. The highest emissions were associated with crop residues, agrochemical production, and fuel use. Over 50% of emissions in soybean farming were attributed to soil N2O, mainly from crop residues, according to the Greenhouse Gases, Regulated Emissions, and Energy Use in Technologies (GREET) model. Emissions from soybean oil production were estimated at 149.72 kgCO2eq per ton of oil, consistent with previous studies. For soybean meal production, emissions resulted in 73.57 kgCO2eq per ton of meal, with 66.1% attributed to natural gas consumption. This study provides a comprehensive evaluation of GHG emissions across the soybean production chain. Its results can support decision making for emission reductions in key stages of the process.